PENGGUNAAN BAHASA GAUL TERHADAP ETIKA REMAJA DALAM PANDANGAN ISLAM - A'eni, Nur; Apriani, Hamidah (Sekolah Tinggi Ilmu Tarbiyah Insan Kamil Bogor, 2025)
The use of slang language among teenagers is a common phenomenon. These unique and creative terms make it easier to communicate and build a sense of togetherness among them. However, in the Islamic view, the use of slang language should also be seen from the ethical and moral aspects that should be upheld by a teenager. By encouraging the use of good, correct, and non-harmful language. The purpose of this study is to educate the public, especially teenagers, to be able to use slang language appropriately in certain situations and conditions. The research method used in this study is a qualitative descriptive approach. The results of the study concluded that the use of slang language by teenagers needs to be addressed wisely and responsibly. The use of slang language among teenagers is not prohibited, but its use must be in accordance with Islamic ethics and teachings